Pendampingan UMKM Kerupuk 32 dalam Meningkatkan Daya Jual dan Pengetahuan Produk Higienis di Kecamatan Bumi Waras Lampung - Yuli Evadianti; Ayu Nadia Pramazuly (Fakultas Ilmu Sosial dan ilmu Politik, 2022)
The purpose of community service to help the Kemplang 32 Cracker Business increase knowledge of hygienic products, so that they can increase the selling power of their products on the market. The Kemplang 32 Kerupuk UMKM is located in the Kemplang Cracker Center and was chosen as one of the assistance because this cracker business produces as much as 100 kg in a day with manual work, starting from making starter, kneading until smooth, printing, steaming to drying. Meanwhile, demand from the three markets, namely Pasar Panjang, Pasar Cimeng and Pasar Kangkung, was more than 100 kg. It is hoped that with the creation of tools and marketing in the market place, production can increase to 200 kg/hr. The approach method for the PKM-UMKM program implemented is situation analysis, formulating problems, formulating solutions to overcome problems, assistance in arranging requirements and registration of product legality permits, increasing production capacity with appropriate technology. The output target of the PKM-UMKM program is to optimally increase the production and selling power of the Kemplang 32 Cracker Business products in the market. If it's not the rainy season, the crackers are also dried in the yard of people's homes, on the rooftops and on the side of the road, motorized vehicles and people walking by. For this reason, assistance is needed in increasing hygienic product knowledge, the solution offered is the use of a simple dryer. In addition, to expand marketing in Indonesia, training is also needed on marketing products on marketplaces, social media, attractive packaging. Keywords: community service, UMKM, selling powe, hyjienic product